Chest x-ray resolution after SARS-CoV-2 infection - Besim Prnjavorac; Aida Mujaković; Lejla Prnjavorac; Tamer Bego; Edin Jusufović; Edin Begić; Vildana Torlak-Arnaut; Mutapčić Meliha; Hasan Škiljo; Enes Hodžić; Emina Karahmet; Maja Malenica; et al. (Medicinski glasnik, 2021)
Aim To analyse the resolution of chest X-ray findings in relation to laboratory parameters in patients infected with acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in a two- month follow-up. Analysis of chest X-ray findings in the first few months after the disease is the main goal of our work. Methods Out of the total of 343 patients chest X-ray findings were followed in 269 patients. Patients were divided into groups according to the severity of findings. D-dimer, inflammatory markers, blood cell count, neutrophil lymphocyte ratio (NLR) were analysed. Chest X-ray was analysed during the hospitalization on the day of admission, on the third, the seventh and the fourteenth day (scoring method was used). After discharge chest X-ray was performed in a two-week follow-up, then after one and two months, and after three months if necessary. Results Incomplete chest X-ray resolution was identified in 24 (39.34%) patients with severe, 27 (22.31 %) patients with moderate and in three (3.91%) patients with mild findings. Statistical significance was established in overall score by comparison between all groups (p<0.001), and in the moderate compared to the mild group (p=0.0051). The difference of NLR in the severe compared to the moderate group was observed (p=0.0021) and in the severe group compared to the mild group (p=0.00013). Conclusion Chest X-ray findings persisted mostly in the severe group followed by the moderate and mild ones. Long-term follow-up is necessary for the appropriate treatment and prevention of fibrosis, and reduction of symptoms.
Keywords: COVID-19; fibrosis; inflammation; lung